Proses Perencanaan Terhadap Kegiatan 4th PGA Unsoed Golf Tournament - Anya Amabell Syukuri; Sudarno Sudarno (Bisnis Event, 2020)
The 4th PGA Unsoed Golf Tournament is the 4th Golf tournament event held by PGA Unsoed (Alumni Unsoed) which is an annual event. The business of organizing golf sports tournaments is an event that unites, it can be seen from the goal when playing golf is as a communication place to talk about work and business and every element in the golf tournament such as the committee, general participants, sponsors and elements in their venues playing together, although as a venue race but they compete in family manner. The method used in this writing is the method of observation and literature, namely the authors go directly into work practices and collect information data, theorist based on literature books, websites and lab module. The purpose of this research is to know the preparation for holding a golf tournament. The result of this study are the preparation of a golf tournament long enough if you want to get the desired result. Many businessmen and industries are competing to hold a neat and memorable golf tournament.